Evaluation of Mandibular Infiltration Compared to Mandibular Block Anesthesia in Pediatric Dentistry - Khudair A. Salman Al-Jumaili; Baydaa A. Othman Al-Rawi; Ghaeth H. Yassen (University of Mosul, College of Dentistry, 2009)
Aims: The aim of this study is to determine the effectiveness of mandibular infiltration compared withthe mandibular block in treating mandibular primary molars in children and to relate it to the type oftreatment performed. Materials and Methods: The study design was case control study. The studysample consisted of 98 cooperative children of age 3-9 years old. Forty eight children were the studygroup (infiltration group). Equal number of children to the study group matched for age and genderwere chosen (block group), they had the same criteria of the study group and required the same type oftreatment. Dental procedure included amalgam restorations, foromcresol pulpotomies, and extractions.Evaluations of pain for each anesthesia technique and type of treatment were conducted using sounds;motor and ocular changes indicating pain. Evaluations were made upon probing, during tooth preparation,coronal pulp removal and extraction. Results: No statistically significant difference was foundbetween the two anesthetic techniques of pain, when performing amalgam restorations (p>0.05). Mandibularinfiltration was significantly less effective than mandibular block for pulpotomy and extraction(p<0.05). Conclusions: In this study, the mandibular infiltration was found to be a reliable local anesthetictechnique in amalgam restoration. For pulpotomy and extraction, mandibular infiltration was notas effective as mandibular block. It is recommended to avoid the mandibular infiltration anesthesia,whenever possible for pulpotomy or extraction procedure in primary molars